Concentric and eccentric compression performance of multiple-cell cruciform CFSTs. (May 2022) - Hassam, Muhammad; Guo, Lanhui; Jia, Chen
Abstract: Multiple-cell cruciform concrete-filled steel tube is a novel and efficient category of conventional cruciform concrete-filled steel tubes, mainly suitable for structures requiring high resistance and excellent seismic performance. This paper presents a test study of ten multiple-cell cruciform concrete-filled steel tube specimens, including six stub specimens and four slender specimens under compression. The experiment comprises the following key parameters: tube width-to-thickness ratio, length-to-breadth ratio, and eccentricity ratio. The influence of these factors on peak resistance, failure pattern and ductility were investigated by discussing and analyzing the failure procedure, load-displacement relationships, load-lateral deflection graphs and load-strain relationships. The test results demonstrated that: (1) local buckling was deferred, and the peak resistance was improved for specimens with smaller width-to-thickness ratio; (2) specimens with increment in length-to-breadth ratio or eccentricities had lower compression capacities; (3) the configuration of multiple-cell steel tubes improved the constraint effect significantly. Further, the finite element simulation was performed to determine the behaviors of the specimens and was validated with test results. Based on the parametric analysis, the N–M relationships were obtained considering parameters as the width-to-thickness ratio, slenderness ratio, eccentricity, steel grade and concrete strength. The concentric and eccentric compression capacity of multiple-cell cruciform concrete-filled steel tubes was predicted by current design codes. At last, the equations to calculate the compression capacity under concentric or eccentric loads were suggested, which were verified by the experimental and simulation results. Highlights: Compression tests on stub and slender MC-C-CFSTs subjected to concentric and eccentric loading are conducted. FE models using ABAQUS are established to study structural behavior of MC-C-CFSTs. The behavior of MC-C-CFSTs with different parameters are investigated. Equations are proposed to precisely estimate the peak-loads.